Drug utilization in neonatal setting of Pakistan: focus on unlicensed and off label drug prescribing - Muhammad Aamir; Jamshaid Ali Khan; Faisal Shakeel; Rabeea Shareef; Nazia Shah (BMC, 2018)
Abstract Background Unlicensed and off label drug use is an issue recognized worldwide in pediatric pharmacotherapy. The study was designed to assess the prevalence and predictors of unlicensed and off label drug use in neonatal population of Pakistan. Method A prospective, observation study was conducted in nursery units at pediatric department of four tertiary care hospitals during the 1 year. Micromedex DRUGDEX was used to evaluate the case notes of 1300 patients. Logistic regression was employed to calculate the odds ratio for the predictors of unlicensed and off label drug use. Results A total of 1300 patients were included in this study who were treated with 52 different drugs. The prevalence of off label drug use was higher (52.14%) as compared to unlicensed drug use (33.35%). Dose (61.29%) and indication (13.68%) were the most frequent reasons for off label prescribing. In comparison to the corresponding reference categories, females and preterm infants were less likely to receive unlicensed prescriptions. While patients staying at hospital more than 5 days and infants receiving 3 or more medications were significantly more likely to receive unlicensed prescriptions. Moreover, in comparison to the corresponding reference categories, females were less likely to receive off label prescriptions while infants receiving 3 or more medications were 7 times more likely to receive off label prescriptions. Conclusion The significant prevalence of unlicensed and off label drug prescriptions was found in neonatal population of Pakistan. The findings imply that more data on prevalence of unlicensed and off label prescriptions are required to provide a better picture of pediatric therapy in developing countries. Furthermore, advance formulations with new dosing in pediatrics is also necessary to minimize the risk of adverse drug events.